BENCANA ITU INDIVIDUALISM (Mencari Identitas Manusia Kristiani dan Perutusan Pelayanannya dalam Bingkai Refleksi Teologi Pastoral) - Tomas Lastari Hatmoko (Aggiornamento, 2021)
In this article, the author would like to see the disaster in relation to the development of individualism, especially in the situation of the Covid-19 pandemic crisis. The disaster is not meant by natural situations, but rather sees the human factor as a source of disaster when each one lives individualism. Furthermore, the author explores and reflects on this theme in pastoral theology. In this way, the search for the identity of the Christian human finds its meaning in the life of Jesus, the Church, and its teachings, including the challenges today. When reflecting on the life of Jesus himself, the christian humans basically cannot be separated from the lifestyle of His service. Therefore, every follower of Christ is called to imitate Him as a person who dares to break the limits of marginality in the mission. Hereafter, the lifestyle of Jesus seems to have inspired the life of the early congregation and the Church until now. In the next discussion, pastoral theological reflection applies the documents of the Second Vatican Council and several documents later. The method used in this paper refers to library research. The results of this study found that individualism is a real disaster that exists in the modern world today. Individual, indifferent, and selfish attitudes have become a source of conflict and misery. This is even more alarming, when during the Covid-19 pandemic people became less concerned. Therefore, every Christian is called to witness, care for others, and cooperate according to the example of Jesus’ life.